Periods of Tribonacci sequences and elliptic curves - AIt-Amrane, L.; Belbachir, H. (Algebra and Discrete Mathematics, 2018)
We will study the periods of Tribonacci sequences associated to elliptic curves. This work is motivated by a paper of Coleman et al. who did it for classical Fibonacci sequences. We are convinced that similar results modulo a deeper work are accessible. Our aim is to explore the Tribonacci case.